2022
DOI: 10.1039/d2ra03175b
|View full text |Cite
|
Sign up to set email alerts
|

Research on the on-line determination of formaldehyde gas by the gas–liquid phase chemiluminescence method

Abstract: Based on the gas–liquid phase chemiluminescence tester independently developed by our laboratory, a highly sensitive, fast and accurate on-line detection method of formaldehyde gas in ambient atmosphere is established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…CL has been widely used in clinical diagnosis, food safety, gas detection, and other elds. [1][2][3] Mikuška successfully detected NO 2 gas in the environment by adding a variety of compounds and surfactants to Luminol. 4 Studies have also demonstrated that O 3 and CO 2 can be monitored in real time by the CL method.…”
Section: Introductionmentioning
confidence: 99%
“…CL has been widely used in clinical diagnosis, food safety, gas detection, and other elds. [1][2][3] Mikuška successfully detected NO 2 gas in the environment by adding a variety of compounds and surfactants to Luminol. 4 Studies have also demonstrated that O 3 and CO 2 can be monitored in real time by the CL method.…”
Section: Introductionmentioning
confidence: 99%